Gun Violence in Montréal : Context, Causes, Reactions, and Recommendations - Pettem, Alexandre (Youth for Youth Québec (Y4Y Québec), 2021)
Montréal has recently been experiencing an unprecedented spike in gun violence, primarily perpetrated by a younger demographic. These shootings are occurring more frequently in broad daylight, in the midst of populated urban areas (Magder). As of August 31, the Montréal police (the SPVM) had documented 77 separate firearms being discharged, with 360 bullets being fired in roughly 100 shootings. This has already surpassed total instances for 2019 and 2020. 654 firearms have been seized, furthermore, the highest ever for the SPVM. This has led to 23 homicides, which is already rapidly approaching the 25 that were observed in both 2019 and 2020 (Perron).